Declaration and Covenant: A comprehensive Review of Covenant Formulae from the Old Testament and the Ancient Near East - Ficker, Rudolf (Journal of Dharma, 1984)
Paul Kalluveettil Declaration and Covenant A comprehensive Review of Covenant Formulae from the Old Testament and the Ancient Near East : Analecta Biblica 88, Rome (1982) Biblical Institute Press, XI, 284 p; bibliography (pp 214-235) and indices (Scripture references, OT words, ANE words, modern authors, general).